1990
DOI: 10.2337/diab.39.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Structure and Plasma ANF Levels in Rats With Chronic Diabetes Mellitus

Abstract: The effect of streptozocin-induced diabetes (STZ-D) on right atrial structure was investigated in male Wistar rats. STZ (55 mg/kg) or saline (1 ml/kg) was administered by intravenous injection 12 wk before the experimental studies. Tissue was sampled from four regions of the atrium, processed, and embedded in plastic. Quantitative stereological analysis indicated that in STZ-D rats, there was a significant diminution in size of the musculi pectinati (muscular ridges), which form a network making up the wall of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Our results have shown that ANP concentration in blood plasma was significantly increased in STZ‐treated rats. These findings are in line with previous studies, which showed increases in ANP concentrations after different periods of STZ treatment ranging from 1 week to 8 months 10–13,20–24 . Plasma ANP concentrations have been shown to rise with acute hyperglycemia in human type 1 and type 2 diabetes 7 , 25 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results have shown that ANP concentration in blood plasma was significantly increased in STZ‐treated rats. These findings are in line with previous studies, which showed increases in ANP concentrations after different periods of STZ treatment ranging from 1 week to 8 months 10–13,20–24 . Plasma ANP concentrations have been shown to rise with acute hyperglycemia in human type 1 and type 2 diabetes 7 , 25 .…”
Section: Discussionsupporting
confidence: 92%
“…Plasma ANP concentrations have been reported to be either increased 6 or normal 7 in type 1 diabetic patients compared with normal subjects. The concentrations in chronic streptozotocin (STZ)‐diabetic rats have also been shown to increase 8–11 though unaltered plasma ANP concentrations have been reported 12,13 . It is still not clear whether the increase in plasma concentration is due to increase in cardiac ANP secretion.…”
Section: Introductionmentioning
confidence: 99%
“…For our study we used rats that had undergone coronary ligation 8 weeks after the induction of diabetes. We chose this experimental period because previous reports had demonstrated that atrial levels of ANP mRNA remained unchanged for 8 weeks after STZ injection and that no apparent cardiomyopathy existed at that time (Todd et al, 1990 In our study, we found a significant increase in atrial expression of BNP in diabetic rats, but no effect in RV and LV. Tb previous report mentioned that atrial granularity, which includes ANP protein, was significantly decreased (by 39) in short-term (6 wk duration) STZ-induced diabetes in rats, but no evidence of ventricular cardiomyopathy (Hebden RA, at al, 1989).…”
Section: Reversibility Ti'ith Insulin Therapysupporting
confidence: 50%
“…Chronic poor glycaemic control predicts the future development of overt nephropathy in Type 1 diabetes[11], and studies consistently report that plasma ANP concentrations rise acutely with the onset of hyperglycaemia in rats rendered diabetic by streptozotocin[1,12–16]. However, the evidence in humans is conflicting.…”
Section: Introductionmentioning
confidence: 99%